THE ART OF TELLING THE TRUTH TO DECEIVE: A MATTER OF INTENT - Narcisa PRODAN; Laura VISU-PETRA (Studia Universitatis Babes-Bolyai, 2022)
When deciding to deceive, individuals carefully consider others' mental states to determine how their statements will be perceived by the recipient. In highly competitive contexts, deceptive intentions might be anticipated by others, so the use of false information to deceive might not be successful. Instead, using the truth can be a better strategy, anticipating that the recipient would consider the statements to be false. The present paper discusses the literature to date investigating the ability to tell the truth to deceive others in relation to the socio-cognitive processes that support it. We examine the emerging literature by discussing the differences between simple deception, sophisticated deception, and paltering. However, the lack of sophistication regarding the use of true vs. false information to deceive restricts the ecological validity of the findings. We propose a more elaborate truth-telling for deceptive purposes approach related to socio-cognitive correlates, such as theory of mind. Received: 2022 March 05; Revised: 2022 March 25; Accepted: 2022 March 28; Available online: 2022 May 5; Available print: 2022 May 30